LEGAL IMPLEMENTATION OF CYBER NOTARY REGULATION: IMPLEMENTATION OPPORTUNITIES AND LEGAL CHALLENGES IN INDONESIA - Mirabel Rahma Nesiabila; Mochamad Fachrurozi; Edi Anggara Febriana; Ratu Citra Fatihanisa; Azriel Chayrul Fabian has; Alya Putri Nasution; Aurelllia Dianti (Ann Publisher, 2025)
Abstract Background. This study reviews how regulations related to cyber notaries are implemented in Indonesia. The main focus lies in the effectiveness of implementation and the gap between the potential use of cyber notary technology and the lack of optimal regulations that regulate it as a whole. Although the Electronic Information and Transaction Law (ITE Law) has become the legal basis, the lack of technical regulation still makes the implementation of cyber notary vulnerable to legal uncertainty. Aims. This study also analyzes the fundamental differences in the concept of cyber notary in civil law legal systems such as Indonesia and common law, which underlines the importance of appropriate regulatory adjustments. The issue of electronic data security is a major concern, so clear rules are needed regarding electronic certification and institutions that have the authority to regulate it. Methods. This research uses a qualitative approach with a descriptive method in data collection and analysis. Conclusion. The study's conclusion shows that although cyber notaries have great potential to increase efficiency and effectiveness in the notary field, more complete and systematic regulations are needed to ensure data security, the validity of electronic documents, and legal certainty in Indonesia. Implementation. The application of this technology is an important step in balancing the development of digitalization, which needs to be realized immediately in order to encourage modernization in notary practice.